The Impact of Advanced Preprocessing Techniques on Machine Learning Models for Income Prediction - Abu Sara, Mutaz Rasmi; Emaya, Andres (Ahliya Journal of Business Technology and MEAN Economies, 2026)
Data preprocessing plays a fundamental role in improving the reliability and predictive performance of machine learning models, particularly when dealing with real-world tabular datasets containing missing values, outliers, redundant features, skewed distributions, and heterogeneous data types. This study investigates the impact of advanced preprocessing techniques on income prediction using the Adult Income dataset. A comprehensive preprocessing pipeline was developed by integrating missing value imputation, variance-based feature selection, IQR-based outlier treatment, Yeo–Johnson transformation, standard scaling, one-hot encoding, Singular Value Decomposition (SVD), and a Column Transformer-based workflow to eliminate data leakage. Four machine learning models—Histogram-Based Gradient Boosting (HistGB), Random Forest, Logistic Regression, and Linear Support Vector Classifier—were trained and evaluated using stratified k-fold cross-validation and an 80/20 train-test split. Performance was assessed using Accuracy, Precision, Recall, F1-score, ROC-AUC, and Log-loss. The results demonstrate that the proposed preprocessing pipeline consistently improved the performance of all models, with Histogram-Based Gradient Boosting achieving the highest test accuracy of 86.8% and a ROC-AUC of 92.1%, indicating excellent predictive capability and strong generalization with minimal overfitting. The originality of this study lies in the development of a unified and reproducible preprocessing framework that systematically integrates multiple advanced preprocessing techniques and applies them consistently across different machine learning models, enabling a fair comparative evaluation. Unlike previous studies that primarily emphasize algorithm selection, this research demonstrates that a carefully designed preprocessing pipeline can substantially enhance predictive performance and produce competitive results without relying on complex ensemble architectures or extensive model tuning.